Cooperative behavior and knowledge sharing: interaction of risk management - Mannes, Silvana; Beuren, Ilse Maria; Souza da Silva, Evelise (Review of Business Management, 2022)
Purpose – This study analyzes the influence of cooperative behavior and organizational risk management on knowledge sharing in Brazilian agricultural cooperatives. Complementarily, it analyzes the interaction of organizational risk management in the relationship between cooperative behavior and knowledge sharing. Theoretical framework – The research is based on the literature on cooperative behavior, organizational risk management, and knowledge sharing with variables derived from previous literature. Methodology – A survey was conducted with strategic level managers in Brazilian agricultural cooperatives, with the sample being composed of 104 valid responses. To test the hypotheses, the structural equation modeling technique was applied. Findings – The results show that cooperative behavior positively and significantly influences risk management and knowledge sharing; however, no statistical significance was found in the relationship between risk management and knowledge sharing. This indicates that higher levels of cooperative behavior are reflected in greater risk management, which helps to mitigate risks, and in greater knowledge sharing in the cooperatives studied. Practical & social implications of research – It presents new information relating to cooperative behavior and risk management in knowledge sharing in cooperatives that integrate strategic alliances. As practical implications, it is highlighted that knowledge sharing should not be perceived as an immediate risk, but as being inherent to cooperation and collaboration between parties. Originality/value – It contributes to the literature by presenting new implications of cooperative behavior and risk management, perceived as enablers of knowledge sharing. Keywords – cooperative behavior; risk management; knowledge sharing; cooperatives.